OMPdb: A Global Hub of Beta-Barrel Outer Membrane Proteins - Roumia, Ahmed F.; Tsirigos, Konstantinos D.; Theodoropoulou, Margarita C.; Tamposis, Ioannis A.; Hamodrakas, Stavros J.; Bagos, Pantelis G. (Frontiers in Bioinformatics, 2021)
OMPdb (www.ompdb.org) was introduced as a database for β-barrel outer membrane proteins from Gram-negative bacteria in 2011and then included 69,354 entries classified into 85 families. The database has been updated continuously using a collection of characteristic profile Hidden Markov Models able to discriminate between the different families of prokaryotic transmembrane β-barrels. The number of families has increased ultimately to a total of 129 families in the current, second major version of OMPdb. New additions have been made in parallel with efforts to update existing families and add novel families. Here, we present the upgrade of OMPdb, which from now on aims to become a global repository for all transmembrane β-barrel proteins, both eukaryotic and bacterial.